Size inequality dynamics and allometric model for estimating the self-thinning exponent in overcrowded mangrove Kandelia obovata forest - Analuddin, Kangkuso; Sharma, Sahadev; Hagihara, Akio (International Journal of Science, Engineering, and Sustainable Technology (IJSESTech), 2014)
Size inequality dynamics and allometric model of the self-thinning exponent of a crowded mangrove Kandelia obovata stands were analyzed by using five years data. Size variability and skewness of tree height, H and stem diameter of H, D0.1H, as well as the contributions of H and D0.1H on the tree mass, wT variation were analyzed. The Standard deviation SD of H decreased significantly by the vicinity of zero with stand growth, indicating that the variation of H becomes small as the stands grow, and finally all trees may have a similar height. On the other hand, SD of D0.1H was stable as the stands grew, while, the coefficient of variation CV of H significantly decreased as the stands grew. These results suggest that the size inequalities of H and D0.1H become small as the stands grow. Most of the skewness b1-values of H were negative meaning that most of the frequency distributions of H is J-shaped though stands grow. The self-thinning exponent was well-described by Weller’s allometric model, at which the value of  (8) was the same with  (1). This is because the value of  was nearly equal to 1/3, and the value of  was almost zero. Thus, the present study divulged that the size inequality of crowded mangrove actively self-thinned was dynamics, though their biomass density was significantly constant with the progress of time.